2014
DOI: 10.5664/jcsm.3862
|View full text |Cite
|
Sign up to set email alerts
|

Short Duration of Sleep Is Associated with Elevated High-Sensitivity C-Reactive Protein Level in Taiwanese Adults: A Cross-Sectional Study

Abstract: Background: Elevated plasma levels of high-sensitivity C-reactive protein (hs-CRP) have been associated with increased adverse health outcomes. The aim of this study was to investigate the association of sleep duration with risk of elevated hs-CRP levels in Taiwanese adults. Methods: We examined the association between sleep duration and hs-CRP in 353 healthy adults recruited from the physical examination center at a regional hospital in southern Taiwan. Elevated hs-CRP was defi ned as a plasma level ≥ 0.20 mg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 45 publications
3
36
0
1
Order By: Relevance
“…To date, there have been inconsistent results about the relationship between sleep duration and serum hsCRP. Several previous studies have shown that a shorter sleep duration was associated with higher levels of CRP [20,21]. The longitudinal Whitehall II study [21] on London-based office employees aged 35-55 years showed that shorter sleep duration (≤ 5 h) and decreased sleep duration was significantly associated with higher levels of CRP.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…To date, there have been inconsistent results about the relationship between sleep duration and serum hsCRP. Several previous studies have shown that a shorter sleep duration was associated with higher levels of CRP [20,21]. The longitudinal Whitehall II study [21] on London-based office employees aged 35-55 years showed that shorter sleep duration (≤ 5 h) and decreased sleep duration was significantly associated with higher levels of CRP.…”
Section: Discussionmentioning
confidence: 96%
“…Although previous studies have investigated the association between sleep duration, hsCRP, and SUA, the results were inconsistent [20][21][22][23][24]. Some studies found that short sleep duration was associated with elevated CRP [20,21]. Richardson et al [22] showed that short sleep duration was significantly associated with elevated CRP only in men not in women.…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, recent studies have shown several novel CVD risk factors, such as adipokine leptin9, adiponectin10, and inflammatory marker high-sensitivity C-reactive protein (hs-CRP)11, being linked to short sleep duration. On the other hand, these cardio-metabolic factors have also been found to contribute to cardiac abnormalities, even in the youth, with early changes of cardiac geometry and function121314.…”
mentioning
confidence: 99%
“…Lack of sleep is also associated with various metabolic disorders, as it enhances sympathetic activity, boosts catecholamine levels, and inhibits pancreatic function, thereby reducing insulin secretion. Current studies have shown that increased levels of inflammatory factors and mediators in patients with sleep disorders, including tumor necrosis factor-a, IL-6, IL-8, high-sensitivity C-reactive protein, transcription factors, and adhesion factors, may affect human health through low-grade inflammation pathways (51,52). Increased levels of inflammatory factors are involved in the promotion of insulin resistance by sleep disorders (53).…”
Section: Sleep-related Factorsmentioning
confidence: 99%